Framework of Learning and Upgrading in Global Value Chains - Sourish Dutta (ZBW - Leibniz Information Centre for Economics, 2018)
Echoing Antràs & Rossi-Hansberg (2009), there is a much scope to study the dynamic impact of the international organisation of production on the evolution of knowledge, the distribution of skills, and other country-specific characteristics. This research scope indeed brings my attention to the synergies between different areas of GVCs. Now it would be logical to examine India's efforts to identify trade competitiveness (mainly measured in value added), performance in GVC integration (economic & social upgrading), and the role of country characteristics, including the business climate, investment climate, and drivers of competitiveness across economic, regulatory, operational, and infrastructural dimensions. This study is all about the global value chains of India's manufacturing industries. Of course, these do not only contain activities in the manufacturing sector, but also in other sectors, i.e., agriculture, utilities, and business services that provide inputs at any stage of the production process of manufactures. These indirect sectoral contributions are sizeable and will be explicitly computed through the modelling of input-output linkages across industries. This study could be developed through a most extensive range of available and applicable methodologies followed by an in-depth assessment and discussion of the identified challenges and opportunities.
Keywords: F0; F1; F2; 330; Global Value Chains; Global Production Network; International Trade; Firm-level Trade